The Principle of Proportionality in Armed Conflict under International Law and Islam - Yulianto, Rohmad Adi; Mufid, Abdul (Universitas Islam Negeri Jakarta, 2025)
Proportionality plays a critical role in limiting the harms caused by armed conflict, particularly those affecting civilians and public infrastructure. However, the implementation of this principle can be challenging due to the uncertainties in customary international law status. This leads to differences in legal interpretation and the lack of transparency in military decision-making. This study investigates the principle of proportionality in armed conflict, focusing on its interpretation and application in international law and Islamic jurisprudence. The research examines the similarities and differences between Islamic jurisprudence and international humanitarian law on targeting, use of force, and treatment of non-combatants and detainees. The paper uses normative legal research methodology to explore the legal foundations and practical implications of proportionality in armed conflict, comparing legal frameworks like the Geneva Conventions, Additional Protocols, the Rome Statute, and Islamic legal literature. The study reveals commonalities and differences between International Humanitarian Law and Islamic law. The findings highlight the crucial role in reducing the impact of armed conflicts on civilians and infrastructure. The study advocates for ongoing dialogue and cooperation to improve global adherence to proportionality in armed conflicts.AbstrakPrinsip proporsionalitas berperan penting dalam membatasi dampak yang ditimbulkan oleh konflik bersenjata, khususnya terhadap warga sipil dan infrastruktur publik. Namun, penerapan prinsip ini menghadapi berbagai tantangan akibat ketidakpastian statusnya dalam hukum kebiasaan internasional. Hal ini menyebabkan perbedaan dalam interpretasi hukum serta kurangnya transparansi dalam pengambilan keputusan militer. Penelitian ini mengkaji prinsip proporsionalitas dalam konflik bersenjata, dengan fokus pada interpretasi dan penerapannya dalam hukum internasional dan yurisprudensi Islam. Selanjutnya, studi ini menganalisis persamaan dan perbedaan antara yurisprudensi Islam dan hukum humaniter internasional dalam hal penargetan, penggunaan kekuatan, serta perlakuan terhadap non-kombatan dan tahanan. Dengan menggunakan metode penelitian hukum normatif, studi ini mengeksplorasi landasan hukum serta implikasi praktis dari prinsip proporsionalitas dalam konflik bersenjata, melalui perbandingan berbagai kerangka hukum seperti Konvensi Jenewa, Protokol Tambahan, Statuta Roma, dan literatur hukum Islam. Penelitian menunjukkan adanya titik temu dan perbedaan antara Hukum Humaniter Internasional dan hukum Islam. Temuan ini menekankan pentingnya prinsip proporsionalitas dalam mengurangi dampak konflik bersenjata terhadap warga sipil dan infrastruktur. Studi ini mendorong adanya dialog dan kerja sama berkelanjutan untuk meningkatkan kepatuhan global terhadap prinsip proporsionalitas dalam konflik bersenjata.